The impact on urology residents’ learning of social media and web technologies after the pandemic: a step forward through the sharing of knowledge - Rodler, Severin; Bujoreanu, Cristina Eliza; Baekelandt, Loic; Volpi, Gabriele; Puliatti, Stefano; Kowalewski, Karl-Friedrich; Belenchon, Ines Rivero; Taratkin, Mark; Rivas, Juan Gomez; Veccia, Alessandro; Piazza, Pietro; Carrion, Diego M.; et al. (Healthcare, 2023)
The COVID-19 pandemic has impacted urology residents and their training. However, several new technologies or knowledge platforms as social media (SoMe) and web-based learning solutions have filled this gap. Therefore, we aimed to analyze resident’s learning curves of new learning modalities, identify the evidence that is provided in the literature, and evaluate the possible impact of such solutions in the future. We conducted a non-systematic literature search using Medline, PubMed, and Embase. In addition, online resources of national and international urology resident societies were queried. The identified paper described SoMe, webinars, podcasts, pre-recorded surgical videos, educational platforms, and mobile apps in the field of urology that are used to gain access to information, teach and provide feedback to residents, and were used under the conditions of the pandemic. The application of those technologies harbors the risk of mis- and disinformation, but have the potential to provide access to education and validated knowledge, training, and feedback and thereby might democratize training of residents in urology globally.
Veröffentlicht: 25. Juni 2023
Gesehen am 23.08.2023